Energy and exergy efficiency of a flat plate solar collector using pH treated Al2O3 nanofluid. (20th January 2016) - Said, Z.; Saidur, R.; Sabiha, M.A.; Hepbasli, A.; Rahim, N.A.
Abstract: Application of nanofluid to increase the thermal efficiency of a traditional solar collector is getting tremendous attention among the scientific community. Al2 O3 –water nanofluid, as a working fluid and its effect on the energy and exergy efficiencies of a flat plate solar collector was examined experimentally. Volume fraction used for this study was 0.1% and 0.3%, while the size of the nanoparticles was ∼13 nm. Experiments were carried out using a stable nanofluid which was obtained by controlling the pH of the solution over a period of 30 days. The mass flow rates of the nanofluid varied from 0.5 to 1.5 kg/min. Energy and exergy efficiencies of a flat plate solar collector using water and nanofluids as working fluids were matched. The results revealed that nanofluids increased the energy efficiency by 83.5% for 0.3% v/v and 1.5 kg/min, whereas the exergy efficiency was enhanced by up to 20.3% for 0.1% v/v and 1 kg/min. Thermal efficiency of the system was found to be more than 50% compared to the existing system available in the literature. New findings on the stability and exergy analysis of the solar collector system operated with a pH controlled nanofluid are reported. Highlights: Stable nanofluids suspension achieved using controlled pH. Thermal conductivity surges up to 6.8% with 0.3 vol. % of Al2 O3 . Higher energy and exergy efficiency with Al2 O3 –H2 O nanofluid. The energy efficiency improved by 83.5% for 0.3% volume fraction and 1.5 L/min. The exergy efficiency is enhanced by up to 20.3% for 0.1% volume fraction and 1 L/min.